Prediction and optimization model of activated carbon double layer capacitors based on improved heuristic approach genetic algorithm neural network. Issue 4 (11th June 2018) - Yang, Zhen; Lin, Yun; Gu, Xingsheng; Liang, Xiaoyi
Abstract : Purpose: The purpose of this paper is to study the electrochemical properties of electrode material on activated carbon double layer capacitors. It also tries to develop a prediction model to evaluate pore size value. Design/methodology/approach: Back-propagation neural network (BPNN) prediction model is used to evaluate pore size value. Also, an improved heuristic approach genetic algorithm (HAGA) is used to search for the optimal relationship between process parameters and electrochemical properties. Findings: A three-layer ANN is found to be optimum with the architecture of three and six neurons in the first and second hidden layer and one neuron in output layer. The simulation results show that the optimized design model based on HAGA can get the suitable process parameters. Originality/value: HAGA BPNN is proved to be a practical and efficient way for acquiring information and providing optimal parameters about the activated carbon double layer capacitor electrode material.